Systematic Country Diagnostic for the Eight Small Pacific Island Countries : Priorities for Ending Poverty and Boosting Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2016)
This Systematic Country Diagnostic (SCD) covers eight small Pacific island countries (PIC8): Kiribati, Marshall Islands, the Federated States of Micronesia, Palau, Samoa, Tonga, Tuvalu, and Vanuatu. The objective of the SCD is to identify the most critical constraints and opportunities facing the PIC8 to meet the global goals of ending absolute poverty and boosting shared prosperity in a sustainable manner. The report is intended to help these countries, the World Bank and other development partners establish a dialogue to focus their efforts around the key priorities and activities that have high impact and are aligned with the two goals. The regional approach of this SCD is driven by the similarity of development challenges faced by these countries and the importance of regional solutions to these challenges. The SCD also highlights that economic opportunities available to the Pacific island countries are limited. While these opportunities have been known for a long time, the experience of most of these countries in realizing these opportunities has been disappointing, reflected in the poor growth performance of the PIC8. A realistic assessment of these opportunities as well as of the measures needed to realize them is essential. In this context, deep sea mining is seen by some of the PIC8 as the next big opportunity, while at the same time many raise concerns about its possible environmental impacts. This is thus an area that would benefit from an objective assessment of risks and opportunities that could inform policy choices in the PIC8. With the liberalization of telecoms markets and investments in fiber-optic cables that connect many of the PIC8, new opportunities to overcome the tyranny of distance through a focus on knowledge products may become available and deserve a critical assessment. The Pacific Possible research program led by the World Bank Group is providing new insights into the potential of these game-changers.